SINTESIS KARBOKSIMETIL SELULOSA (CMC) DARI SELULOSA KULIT DURIAN (Durio zibethinus) - Dini Safitri; Erwin Abdul Rahim; Prismawiryanti Prismawiryanti; Rismawati Sikanna (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
The investigation about of carboxymethyl cellulose (CMC) of Durian peel (Durio zibethinus) cellulose has been done. The research aim is to determine the best ratio of sodium mono-chloroacetate toward cellulose and is to determine the reaction time in the synthesis of carboxymethyl cellulose of durian peel in order to obtain the highest substitution degree. The applied of ratio variations and reaction time were 5:5, 6:5, 7:5, 8:5, 9:5 grams and 1, 2, 3, 4, 5, respectively. The result showed that the best ratio of sodium mono-chloroacetate toward cellulose was 7:5 gram with yields and the substitution degree of 39.39% and 1.17, respectively. The best time reaction was found at 4 hours with yields and the substitution degree of 39.77 % and 1.2, respectively. Keywords: Durian peel, carboxymethyl cellulose, substitution degree.